I am Scout : the biography of Harper Lee - Shields, Charles J., 1951- (New York : Henry Holt, 2008)
An exploration of the life and achievements of Harper Lee that discusses her Southern upbringing, education, family, writing of "To Kill a Mockingbird," association with Truman Capote, and personality.
Includes bibliographical references (p. [213]-239) and index.
School Library Journal.
Wilson's Junior High School.
Wilson's Senior High School.
Booklist, March 2008.
Bulletin (Center for Children's books), June 2008.
Keywords: Lee, Harper -- Juvenile literature; Lee, Harper; Lee, Harper; Authors, American -- 20th century -- Biography -- Juvenile literature; Authors, American -- 20th century; Women -- Biography; American authors -- Biography; Women -- Biography